2009
DOI: 10.1177/0091270009335768
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Pharmacokinetics, and Pharmacodynamics of Single Doses of LXR‐623, a Novel Liver X‐Receptor Agonist, in Healthy Participants

Abstract: Liver X-receptor (LXR) agonists have been postulated to enhance reverse cholesterol transport (RCT), a process believed to shuttle cholesterol from the periphery back to the liver. Enhancing RCT via the upregulation of cholesterol transporters such as the adenosine triphosphate-binding cassettes ABCA1 and ABCG1 could therefore inhibit the progression of atherosclerosis. LXR-623 is a synthetic ligand for LXRs alpha and beta that has shown promise in animal models of atherosclerosis. The authors present results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
116
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(123 citation statements)
references
References 28 publications
3
116
0
2
Order By: Relevance
“…Along with the natural function in lowering plasma cholesterol, it did not appear to have the adverse side effects seen with other LXR agonists. LXR-623 (2-[(2-chloro-4-fluorophenyl) methyl]-3-(4-fluorophenyl)-7-(trifluoromethyl)indazole), an indazole, was also tested in the first reported phase 1 clinical trials; it had adverse CNS side effects, so the study was terminated (DiBlasio-Smith et al, 2008;Katz et al, 2009).…”
Section: Selective Liver X Receptor Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the natural function in lowering plasma cholesterol, it did not appear to have the adverse side effects seen with other LXR agonists. LXR-623 (2-[(2-chloro-4-fluorophenyl) methyl]-3-(4-fluorophenyl)-7-(trifluoromethyl)indazole), an indazole, was also tested in the first reported phase 1 clinical trials; it had adverse CNS side effects, so the study was terminated (DiBlasio-Smith et al, 2008;Katz et al, 2009).…”
Section: Selective Liver X Receptor Modulatorsmentioning
confidence: 99%
“…WAY-252623 (LXR-623) (Fig. 13) is one such indazole-based selective LXR modulator with an IC 50 of 179 and 24 nM for LXRa and LXRb, respectively (Katz et al, 2009). The X-ray structure of LXR-623 bound to LXRb revealed that N-1 indazole nitrogen forms a hydrogen bond with His435, while the 7-trifluoromethyl group makes electrostatic interactions with the same residue; this makes it different from GW3965 and explains its good in vivo efficacy .…”
Section: Selective Liver X Receptor Modulatorsmentioning
confidence: 99%
“…LXR agonists, on the other hand, are not approved for clinical use in humans. The LXR agonist TO-901317 was tested in a clinical trial for the treatment of atherosclerosis and hyperlipidemia; however, the trial was discontinued due to unexpected neurotoxicity after systemic administration (33,74). In a topical preparation, however, the systemic adverse effects associated with NR ligand administration might be limited.…”
Section: Nr Ligands Inhibit Hiv-1 Replication In Primary Macrophagesmentioning
confidence: 99%
“…LXR-623, a tissue-specific ligand that activates LXR with limited hepatic liability, was also disappointing; central nervous system-related adverse events were observed in the first-in-humans clinical trial (Katz et al, 2009). Therefore, it is essential to identify selective LXR agonists or antagonists that have beneficial effects on the target tissue with minimal unwanted effects on off-target tissues.…”
Section: Discussionmentioning
confidence: 99%